5t-3t-14=0

Simple and best practice solution for 5t-3t-14=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t-3t-14=0 equation:


Simplifying
5t + -3t + -14 = 0

Reorder the terms:
-14 + 5t + -3t = 0

Combine like terms: 5t + -3t = 2t
-14 + 2t = 0

Solving
-14 + 2t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 2t = 0 + 14

Combine like terms: -14 + 14 = 0
0 + 2t = 0 + 14
2t = 0 + 14

Combine like terms: 0 + 14 = 14
2t = 14

Divide each side by '2'.
t = 7

Simplifying
t = 7

See similar equations:

| 3x-4=2(2x+6) | | 2c-5=15 | | 44+20=h | | P+p+o=4 | | 12-s=14 | | 98=-3(-2x-7)+5x | | 25g-5g^2=0 | | -4x+8=-2x+2 | | x+3x=2000 | | 5x(5x-4)= | | -4a+4(3a+3)=-8-2a | | 2y=6(-2)-10 | | p+1.6-0.4=-12 | | 2x+5y+2z=10.50 | | -5x^4+20x^2=0 | | 4x=-3x-7 | | 7y+6=180 | | 15=1.25h | | 8+8x+2x=2x+16 | | f(x-1)=x^2-14x+54 | | (2x+3.75)x-0.5=11.5 | | 3*8+2*-2= | | 6(3n-5)=(7n+6)+3 | | 9m^2+2m=10 | | 12+b=10 | | -54=a-49 | | 72=-6m | | Log(t-3)=(17-4t) | | (3x-18)(8x+32)=0 | | .5x^4-.5=0 | | -6p=58 | | -36g+40g+19g+-47g+18g=42 |

Equations solver categories